2018
DOI: 10.1186/s12894-018-0333-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the combination of preoperative hemoglobin and albumin levels and lymphocyte and platelet counts (HALP) in patients with renal cell carcinoma after nephrectomy

Abstract: BackgroundTo evaluate the prognostic significance of the novel index combining preoperative hemoglobin and albumin levels and lymphocyte and platelet counts (HALP) in renal cell carcinoma (RCC) patients.MethodsWe enrolled 1360 patients who underwent nephrectomy in our institution from 2001 to 2010. The cutoff values for HALP, neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio were defined by using X-tile software. Survival was analyzed by the Kaplan–Meier method, with differences analyzed by the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
86
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 30 publications
10
86
0
2
Order By: Relevance
“…The nomogram indicated that age ≥ 36.5, female, coma and straight sinus thrombosis location were the poor prognostic factors, but higher HALP was still a potential good prognostic factor. The results of the nomogram were similar to those of aforementioned multivariate analyses in tumor [10][11][12] .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The nomogram indicated that age ≥ 36.5, female, coma and straight sinus thrombosis location were the poor prognostic factors, but higher HALP was still a potential good prognostic factor. The results of the nomogram were similar to those of aforementioned multivariate analyses in tumor [10][11][12] .…”
Section: Resultssupporting
confidence: 75%
“…It was the integration of these four indexes and relatively more stable than single blood parameters. HALP was closely associated with clinical features and was an independent prognostic factor in several types of malignant tumors, including genitourinary cancer, bladder cancer and renal cell carcinoma [10][11][12] . However, there were no reports concerned with roles of HALP in CVST patients, especially in acute and subacute CVST patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, evaluating the pre‐metastatic stage is meaningful to improve prognosis and assist clinicians in making therapeutic choices. Comprehensive nomograms are useful and convenient tools to evaluate the prognosis of patients and they have been reported for some cancers. In this study, we first constructed prognostic nomograms for patients with non‐metastatic chondrosarcoma based on SEER database and validated them externally.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no study has investigated the association between HALP score and AIS. Recent studies have shown that the HALP score can re ect the in ammation-nutritional status of patients [14,29], and has been proved to be an important prognostic indicator for patients with pancreatic cancer [13], esophageal squamous cell carcinoma [15], and bladder cancer [16]. Anemia and thrombosis could exacerbate in ammation while lymphocytes reduce in ammation [30].…”
Section: Discussionmentioning
confidence: 99%